The Effect of Health Promotion Through Leaflet Media on Mothers’ Behavior Regarding ARI (Acute Respiratory Infection) in Children - Rika Ariyanti; Muh. Idrus; Sitti Marya Ulva (Miracle Journal of Public Health, 2025)
Based on preliminary interviews with mothers of children suffering from acute respiratory infection (ARI), which is an inflammation that affects the throat, nose, and lungs, it was found that many parents still lack a clear understanding of the disease. Initial interviews with mothers at the Southeast Sulawesi Police Clinic, revealed that many parents lack a clear understanding of the disease. This study aims to determine the effect of health promotion through leaflets on mothers’ behavior regarding ARI in children at the clinic. This experimental study used a one-group pretest-posttest design. The population consisted of 49 respondents, and a sample of 33 was selected using accidental sampling. Data were analyzed using a paired-sample t-test. The results showed a significant improvement in mothers’ knowledge, attitudes, and actions concerning ARI in children at the Southeast Sulawesi Police Clinic before and after health promotion using leaflet media. It is hoped that mothers will become more proactive in seeking information about ARI prevention and treatment and will participate in health education activities organized by healthcare facilities.